2021
DOI: 10.1002/jpen.2117
|View full text |Cite
|
Sign up to set email alerts
|

Home parenteral nutrition in older vs younger patients: Clinical characteristics and outcomes

Abstract: Background There is a demographic shift toward older patients receiving home parenteral nutrition (HPN), but data on clinical outcomes are limited. The objective of this study was to determine differences between older and younger HPN patients in regard to HPN indications, prescriptions, and outcomes over the first 2 years receiving HPN. Methods This was a retrospective analysis of prospectively collected data from HPN adult patients entered in the Canadian HPN Registry. New HPN patients enrolled between 2003 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The effect of the changing age distribution on the outcomes of HPN patients' needs to be analyzed in future studies. A retrospective study from Canada showed that older patients on HPN have higher 2-year mortality but a lower risk of catheter-related bloodstream infections [21].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the changing age distribution on the outcomes of HPN patients' needs to be analyzed in future studies. A retrospective study from Canada showed that older patients on HPN have higher 2-year mortality but a lower risk of catheter-related bloodstream infections [21].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the KPS is a graded scale from 0–100 with intervals of 10, and it is able to assess the ability of patients to perform ordinary tasks. This short scale is the one employed by the Canadian HPN Registry because of its convenience for nurses or clinicians to use in busy clinical settings 65 …”
Section: Discussionmentioning
confidence: 99%
“…This short scale is the one employed by the Canadian HPN Registry because of its convenience for nurses or clinicians to use in busy clinical settings. 65 Furthermore, most identified tools were selfadministered and multidimensional, composed of various items. These items were grouped into a variety of subscales or domains, like physical, psychological, social, general health, spiritual, and life condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the propensity for the accrual of signi cant comorbidities in the elderly, there may be issues of poor glycemic control in those with diabetes mellitus and uid/electrolytes issues in those with underlying cardiac and renal impairment 8 . Despite the potential challenges of administering PN in the elderly, recent studies found that home PN is safe in elderly patients with a low risk of catheter related blood stream infections (CRBSI), especially in those who engage home care nursing services 9,10 . While most studies report the safety of long term home PN in medically stable elderly patients in in the community setting [9][10][11] , reported clinical outcomes of elderly patients with acute intestinal failure receiving PN in acute hospital setting remains limited.…”
Section: Introductionmentioning
confidence: 99%